Financial News Sentiment and Investor Confidence: Determinants of Stock Price Volatility in IDX30 - Nuriksan, Sidiq; Nikmah, Nikmah (JOURNAL OF HUMANITIES, SOCIAL SCIENCES AND BUSINESS, 2025)
The purpose of this study is to analyze the effect of financial news sentiment and investor confidence on stock price volatility of 30 companies on the Indonesia Stock Exchange that are members of the IDX30 index. This study uses a quantitative approach and signal theory. The population consists of all companies indexed by IDX30 and sampling using a saturated sample approach or total sampling where all companies indexed by IDX30 are sampled. The Natural Language Processing method is used to measure financial news sentiment and Market to Book Value of Equity to measure investor confidence. Stock price volatility is measured using standard deviation of risk or price volatility. The analysis technique uses multiple regression. The results showed that financial news sentiment affects stock price volatility, and investor confidence has no effect on stock price volatility in IDX30 companies. The results of this study indicate that a small portion of stock price fluctuations are influenced by financial news sentiment and investor confidence levels. The majority of stock price movements are determined by other factors not included in this analysis.